Rapid Assessment of Trees and Shrubs in Sifaran Watershed, Maguindanao Island, Philippines: Implications for Watershed Conservation - Villareal, Jayric Fuentes; Poclis, Cindy Eyop; Sindatok, Abdul Rasheed Nakan; De Vera, Peter Jan Dayrit; Santiago-Arenas, Raquel Doclis; Limbona, Bai Hejira Nefertiti Macalandong (Jurnal Sylva Lestari, 2026)
The Sifaran Watershed is a vital resource for local communities, serving as a water source that flows through the Ligawasan marsh in the Philippines. Despite its critical role, the watershed remains severely understudied. This lack of baseline data has been a major constraint to enacting effective conservation, ensuring the region’s ecological and socio-economic stability. This study focuses on assessing the trees and shrubs thriving in the Sifaran Watershed, as well as their conservation and distribution status. A stratified sampling approach was employed, establishing quadrats across different streams. The study recorded 77 plant species (55 trees and 22 shrubs) across lower, middle, and upper streams, which were largely diverse, with most species categorized as native and of Least Concern by the International Union for Conservation of Nature (IUCN). The presence of native species classified as Vulnerable species (Dracontomelon dao), Near Threatened (Ficus gigantifolia and Macaranga grandifolia), and Endangered (Mangifera odorata, Pterocarpus indicus, and Vitex parviflora) highlights the potential risks from habitat degradation and other threats. While most species exhibit stable populations, conservation efforts are necessary to protect those at risk and maintain the ecological balance of the watershed. The data gathered were utilized as baseline data to provide actionable recommendations for immediate conservation measures and sustainable management, protecting the invaluable natural heritage from threats such as deforestation, land conversion, and climate change. Moreover, initiatives such as habitat reforestation, responsible land use, and the conservation and protection of different species of trees and shrubs, particularly native species, are key to maintaining a balanced and sustainable watershed. Keywords: conservation status, endemic species, least concern species, native species, watershed